Costruire per temi i paesaggi? - Enrica, Dall'Ara (Scuole di dottorato, 2005)
The current diffusion of a design mentality that proceeds by the assignment of themes, in the design of both sites and individual architectural elements, makes it useful to ponder the subject of the theme park that is the purest example of this. More specifically, what this signifies is questioning ourselves about the relations between the natural element, the architecture and the symbol. Addressing the argument with the eye of the landscape architect, it appears dense with repercussions, focusing the question of what landscape we are dealing with and what its design entails. This is an issue of landscape architecture in the purest sense and in its most extreme forms.